The Economic Benefit of Gunung Merapi National Park for the Welfare of the Buffer Village Community - Nurani Dwi Harjanti; Dwiko Budi Permadi; Wahyu Andayani; Tri Atmojo (Jurnal Ilmu Kehutanan, 2024)
Gunung Merapi National Park (GMNP) is an inseparable conservation area from the surrounding community, as the buffer village community has used its existing forest resources. Therefore, this research aimed to identify the forest resources used by the buffer village community and assess the economic benefit value generated by GMNP. The economic benefits evaluation adopted the direct use value approach and market prices. The results showed that the community used water, firewood, grass, land, and sand. Utilization was conducted in utilization, traditional, and rehabilitation zones. These resource utilizations generated a value of IDR426,230,560,828/year, significantly contributing to the welfare of the buffer village community.